2004
DOI: 10.1177/0886109903262759
|View full text |Cite
|
Sign up to set email alerts
|

Work and Social Support: Social Workers’ Assessments of Male and Female Clients’ Problems and Needs

Abstract: This study investigated how social workers assess single mothers' and fathers' needs in the areas of paid work and social support. It found that social workers conform to gender "heteronormative" expectations. A father's problems are assessed as being more closely linked to paid work than are a mother's, whereas a mother's problems are assessed as being related to difficulties in the area of social networks.The ways in which social welfare policy emphasizes the opportunities for men and women to share the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
1
10
0
2
Order By: Relevance
“…These examples may exemplify the male breadwinner identity as one expecting and aiming at hard outcomes (paid work), valuing a concrete task-oriented approach, versus the image of a female identity as one expecting and aiming at intermediate outcomes (soft skills and strengthened self-efficacy), and therefore to a higher degree values a softer approach (care and relational work). Further, this may support previous research indicating that social workers might be approaching male and female participants differently (Kullberg, 2004(Kullberg, , 2005Nybom 2013;Tabin & Perriard, 2016).…”
Section: Swsupporting
confidence: 89%
See 1 more Smart Citation
“…These examples may exemplify the male breadwinner identity as one expecting and aiming at hard outcomes (paid work), valuing a concrete task-oriented approach, versus the image of a female identity as one expecting and aiming at intermediate outcomes (soft skills and strengthened self-efficacy), and therefore to a higher degree values a softer approach (care and relational work). Further, this may support previous research indicating that social workers might be approaching male and female participants differently (Kullberg, 2004(Kullberg, , 2005Nybom 2013;Tabin & Perriard, 2016).…”
Section: Swsupporting
confidence: 89%
“…Thus, service users in activation are heterogeneous with extensive, complex problems that require close, comprehensive follow-up. Therefore, social workers 1 play an important role in activation programmes, and gendered views on work, employment and family care may influence their approaches (Baum, 2016;Betzelt, 2008;Djuve, 2008;Kullberg, 2004Kullberg, , 2005Nybom 2013;Tabin & Perriard, 2016; see also Djuve, Kavli, & Hagelund, 2011). Service users' expectations for the programme may also play a role.…”
mentioning
confidence: 99%
“…Vezano uz pružanje formalne podrške, zanimljiva su istraživanja koja ukazuju na diskriminiranje korisnika i ženskog i muškog spola, svake grupe na drugačiji način, zbog tradicionalnih spolnih stereotipa socijalnih radnika (Kullberg, 2002.). Tako je, primjerice, utvrđeno da socijalni radnici različito procjenjuju probleme i potrebe samohranih roditelja u identičnoj situaciji ovisno o tome radi li se o majci ili o ocu (Kullberg, 2004.). Navedeno upućuje na relevantnost uključivanja varijable spola primatelja u razmatranje društvene podrške roditeljima.…”
Section: Uvodunclassified
“…In a number of vignette studies, social workers' understanding of single parents' problems and needs have been shown to favour a gender-stereotype breadwinner model (see, e.g. Kullberg and Fäldt 2008;Kullberg 2004Kullberg , 2005. While the PSS professionals seem more intent on encouraging single fathers to seek jobs, they tend to emphasize single mothers' parenting roles and social relations (Kullberg 2004(Kullberg , 2005.…”
Section: Social Assistance Assessmentsprevious Researchmentioning
confidence: 99%
“…Kullberg and Fäldt 2008;Kullberg 2004Kullberg , 2005. While the PSS professionals seem more intent on encouraging single fathers to seek jobs, they tend to emphasize single mothers' parenting roles and social relations (Kullberg 2004(Kullberg , 2005. Single mothers are more likely to be granted support compared with the fathers (Kullberg 2005).…”
Section: Social Assistance Assessmentsprevious Researchmentioning
confidence: 99%